Pendampingan Progam Membangun Kemandirian Santri Pondok Pesantren Darussalam Sumbersari Melalui Pembiasaan Perilaku Hidup Bersih Dan Sehat - Mochammad Imam Tobroni; Wildan Habibi (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
This research aims to find out the Strategy of Clean Culture Formation in Darussalam boarding school Sumbersari village Kencong subdistrict besieged Kediri district. The type of method carried out in this study is qualitative research, using descriptive analysis approach, research data collection instrument using instruments: initial observation, documentation and interviews of madrasah heads, teachers, janitors and santri Pondok Pesantren Darussalam Sumbersari. After obtaining the necessary data, then the data is described and then analyzed. The results of research conducted by the author showed that the clean culture in the Darussalam Pondok Sumbersari has been going well. The strategies used by Pondok Darussalam Sumbersari in creating a clean and healthy environment are through: The transparency and consistency of leaders, heads of huts and teachers, the joint movement of boarding school santri, habituation through daily hygiene activities and through supervision of the head of the hut and teachers. From the results of research that has been spelt out previously, the author can draw conclusions about the Strategy of Clean Culture Formation in Darussalam boarding school, Sumbersari village Kencong subdistrict besieged Kediri Regency is quite good, where the implementation procedures include: transparency and consistency, movement together with all boarding schools, hygiene activities, supervision, cooperation with other parties (partners), the existence of association activities or related socialization. cleanliness, and the availability of a supportive physical environment. Also supported by the supervision of cleanliness, participatory activities, such as the existence of class pickets, weekly pickets and annual pickets and greening, the existence of socialization or assistance in the cleanliness and education of clean living environment, and supported by the number of lands owned by the pesantren, making this madrasah and pesantren area become beautiful and green.